Efficiency in Brazil's industrial sectors in terms of energy and sustainable development - Camioto, Flávia de Castro; Mariano, Enzo Barberio [UNESP]; Rebelatto, Daisy Aparecida do Nascimento (Elsevier, 2014)
This article evaluates the efficiency of Brazil's industrial sectors from 1996 to 2009, taking into account energy consumption and respective contributions to the country's economic and social aspects. This analysis used a mathematical programming method called Data Envelopment Analysis (DEA), which enabled, from the SBM model and the window analysis, to evaluate the ability of industries to reduce energy consumption and fossil-fuel CO2 emissions (inputs), as well as to increase the Gross Domestic Product (GDP) by sectors, the persons employed and personnel expenses (outputs). The results of this study indicated that the Textile sector is the most efficient industrial sector in Brazil, according to the variables used, followed by these sectors: Foods and Beverages, Chemical, Mining, Paper and Pulp, Nonmetallic and Metallurgical.
Keywords: Industrial sectors; Data envelopment analysis; Sustainable development; Energy